PENEGAKAN HUKUM PIDANA DI BIDANG ILLEGAL LOGGING BAGI KELESTARIAN LINGKUNGAN HIDUP DAN UPAYA PENANGGULANGANNYA - Bambang Tri Bawono; Anis Mashdurohatun (Jurnal Hukum, 2011)
Criminal Law Enforcement in the Field of Illegal Logging for environmental sustainability has not been completed properly, In fact the government was impressed as if keen to eradicate illegal logging, while the court would release him diligently. development of environmental law in Indonesia. Constraints, the Indonesian legal system is still associated with the pattern of claims with losses that are real. Future losses can not be applied in real terms, therefore losses are not yet occurred, is still a problems of law in Indonesia. Illegal logging is highly impact on the state of ecosystems in Indonesia. Logging provides a very adverse impact surrounding communities, and even the world community. Losses caused by forest destruction is not only the economic value of damage, loss of lung Indonesia and the world, global warming, will be followed by climate change such as increased rainfall in some parts of the world, catastrophic floods and landslides, but instead in another hemisphere experiencing a prolonged drought.Keywords : Criminal Law Enforcement, Illegal logging, Environment